2021
DOI: 10.3390/antiox10121948
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Ocular Diseases Associated with Retinal Ganglion Cells Degeneration

Abstract: Ocular diseases associated with retinal ganglion cell (RGC) degeneration is the most common neurodegenerative disorder that causes irreversible blindness worldwide. It is characterized by visual field defects and progressive optic nerve atrophy. The underlying pathophysiology and mechanisms of RGC degeneration in several ocular diseases remain largely unknown. RGCs are a population of central nervous system neurons, with their soma located in the retina and long axons that extend through the optic nerve to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 249 publications
(325 reference statements)
0
41
0
2
Order By: Relevance
“… 6 In order to maintain normal signal transmission, RGCs require a healthy population of mitochondria with adequate biogenesis, transportation, and remodeling. 7 Furthermore, these mitochondria are highly dynamic—they are continuously changing their location, fusion, and fission in order to meet their energetic demand. 8 …”
mentioning
confidence: 99%
“… 6 In order to maintain normal signal transmission, RGCs require a healthy population of mitochondria with adequate biogenesis, transportation, and remodeling. 7 Furthermore, these mitochondria are highly dynamic—they are continuously changing their location, fusion, and fission in order to meet their energetic demand. 8 …”
mentioning
confidence: 99%
“…In addition to causing DNA damage [3], ultraviolet (UV) light can also cause photo-oxidative stress through the production of reactive oxidative species (ROS) [4]. ROS lead to cell damage and aging, resulting in corneal degeneration, lens opacification (cataracts), and the occurrence of eye diseases, including various retinal and optic nerve degenerative diseases, such as glaucoma and age-related macular degeneration (AMD) [5][6][7]. In recent years, with the depletion of the stratospheric ozone layer [8] and the popularity of light-emitting diode (LED) electronic products [9,10], the long-term photo-oxidative stress brought on by the environment to the eyes is bound to increase the prevalence of these degenerative ocular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegeneration caused by ROS is considered a modifiable factor of glaucoma onset and progression [ 13 , 14 ]. ROS is mainly generated by the metabolism of the mitochondria and neutralized by antioxidants [ 15 ]. We previously reported that lower levels of serum biologic antioxidant potential were correlated with higher levels of IOP and with greater visual field loss in primary open-angle glaucoma (PG) [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%